The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/09538259.2020.1737390
|View full text |Cite
|
Sign up to set email alerts
|

Money Creation in the Eurozone: An Empirical Assessment of the Endogenous and the Exogenous Money Theories

Abstract: The aim of this paper is to strengthen our understanding of the money creation process in the Eurozone for 1999-2016 period, through an empirical assessment of two main monetary theories, namely the (Post Keynesian) endogenous money theory and the (Monetarist) exogenous money theory. By applying a VAR and VECM methodology, we analyse the causal relationship among monetary reserves (or monetary base), bank deposits and bank loans. Our empirical analysis supports several propositions of the Post Keynesian endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…The models validate that monetary indicators are chiefly influenced by the industrial production index, bank deposits, and the volume of loans issued by commercial banks. This corresponds with findings from Deleidi and Fontana (2019), Deleidi and Levrero (2019b), Nayan et al (2013b), andMcLeay andRadia (2014), indicating that the influence of monetary policy on monetary indicators is mainly transmitted through interest rates, thereby impacting money demand. Moreover, the examination not only affirms the causality direction but also quantifies and confirms the anticipated long-term associations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The models validate that monetary indicators are chiefly influenced by the industrial production index, bank deposits, and the volume of loans issued by commercial banks. This corresponds with findings from Deleidi and Fontana (2019), Deleidi and Levrero (2019b), Nayan et al (2013b), andMcLeay andRadia (2014), indicating that the influence of monetary policy on monetary indicators is mainly transmitted through interest rates, thereby impacting money demand. Moreover, the examination not only affirms the causality direction but also quantifies and confirms the anticipated long-term associations.…”
Section: Discussionsupporting
confidence: 87%
“…In the United States, Deleidi and Levrero, (2019a) found that bank loans had a determining effect on bank deposits, influencing the monetary base, and underscoring the significance of economic activity and lending activities of commercial banks in shaping the money supply. Likewise, within the Eurozone, Deleidi and Fontana (2019) found that bank loans affected bank deposits, thereby influencing the monetary base, which is consistent with post-Keynesian theory and lends support to the endogenous viewpoint. Lastly, a recent investigation in Japan by Ongan and Gocer (2023) employing nonlinear models demonstrated that internal factors significantly impact Japan's money supply, enriching our understanding of the endogenous nature of money supply and providing tailored insights into Japan's circumstances.…”
Section: Literature Reviewsupporting
confidence: 82%
“…7 Deleidi and Fontana (2019) have empirically proved the validity of the endogenous money theory in the Eurozone for the 1999-2016 period.…”
Section: Introductionmentioning
confidence: 93%